A Study of Modeling Techniques of Building Energy Consumption - Zerroug, A.; Dzelzitis, E. (Engineering, Technology & Applied Science Research, 2020)
Residential energy consumption accounts for more than 40% of the total energy consumed in the world. The residential sector is the biggest consumer of energy in every country, and therefore focusing on the reduction of energy consumption in this sector is very important. The energy consumption characteristics of the residential sector are very complicated and the variables affecting the consumption are wide and interconnected, so more detailed models are needed to assess the impact of adopting efficient and renewable energy technologies suitable for residential applications. The aim of this paper is to review some of the techniques used to model residential energy consumption. They are gathered in two categories: top-down and bottom-up. The top-down approach considers the residential sector as an energy sink and does not take into account the individual end-uses. The bottom-up approach uses the estimated energy consumption of a representative set of individual houses and extrapolates it to regional and national levels. Based on the strengths, shortcomings, and purposes, an analytical review of each technique, is provided along with a review of models reported in the literature.